ANALISIS EFISENSI PRODUKTIVITAS ALAT BERAT PADA PEKERJAAN PENINGKATAN JALAN AKSES BANDARA GEWAYANTANA - Laurensius Oktavianus Alfian; Yosef Nobertus T. Muda; Oktavianus Jori (Program Studi Teknik Sipil, 2022)
In highway construction projects, heavy equipment resources are the main factor. Heavy equipment must be used efficiently, and tool productivity depends on the type or type of tool, work methods, field conditions, and the tame needed to complete a work. This study employed the method of calculating the actual productivity of heavy equipment, namely the calculation of the speed of the machine, the efficiency factor of the tool, and the production capacity of the machine used in accordance with what was happening in the field. This study aimed to determine the value of heavy equipment productivity in the Gewayantana Airport access road improvement project. The productivity value of the asphalt pavement layer work was 1 unit of asphalt finisher = 22.5 m3/hour, 1 unit of tandem roller = 26.25 m3/hour, 1 unit of pneumatic tyred roller = 9.98 m3/hour, 4 units Biga Dump trucks 6 x 4 = 11.2 m3/hour, the productivity of the tool on the work of the aggregate foundation layer A, namely 3 units of Hino dump truck = 29.94 m3/hour. And calculating the work time required for each heavy equipment based on the number of tools available, namely for asphalt pavement layer work: asphalt finisher = 2 days, tandem roller = 2 days, pneumatic tyred roller = 3 days, Biga dump truck = 4 days, on the work of aggregate foundation layer A, namely: Hino dump truck = 3 days. The results of the calculation obtained were real productivity with a factor of working efficiency that was not good enough according to real working time in the field